Improving the working environment for the delivery of safe surgical care in the UK: a qualitative cross-sectional analysis. Issue 1 (24th January 2019) - Baggaley, Alice; Robb, Lydia; Paterson-Brown, Simon; McGregor, Richard J
Abstract : Objectives: The aim of this study was to identify current problems and potential solutions to improve the working environment for the delivery of safe surgical care in the UK. Design: Prospective, questionnaire-based cross-sectional study. Setting/participants: Following validation, an electronic questionnaire was distributed to postgraduate local education and training board distribution lists, the Royal College of Surgeons of Edinburgh (RCSEd) mailing lists and trainee organisations. This consisted of a single open-ended question inviting five open-ended responses. Throughout the 13-week study period, the survey was also published on a number of social media platforms. Results: A total of 505 responders completed the survey, of which 35% were consultants, 30% foundation doctors, 17% specialty trainees, 11% specialty doctors, 5% core trainees and <1% surgical nurse practitioners. A total of 2238 free-text answers detailed specific actions to improve the working environment. These responses were individually coded and then grouped into nine categories (staff resources, non-staff resources, support, working conditions, communication and team work, systems improvement, patient centred, training and education, and miscellaneous). Conclusions: The results of this study have identified a number of key areas that, if addressed, may improve the environment for the delivery of safer surgical care. Common themes that emerged across all grades included: increased front-line staff; a return to a 'firm' structure to improve team continuity; greater senior support; and improved hospital facilities to help staff rest and recuperate. While unlimited funding remains unrealistic, many of the suggestions could be implemented in a cost-neutral fashion and include insightful ideas for remodelling or restructuring the workforce to improve the efficiency of the surgical team. The findings of this study formed the basis of a set of recommendations published by the RCSEd as a discussion paper.